Effectiveness and Efficiency of Various Croping Methods on Rice Crops - Ekaria, Ekaria; Rope, Ranita (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
East Halmahera Regency is one of the areas in North Maluku Province which is a priority in developing and increasing rice production with a harvest area of 3,200. East Wasile District has the largest harvest area compared to other Districts, namely 1,406 and the development of lowland rice plants uses several planting methods, namely conventional planting methods and jajar legowo. This study aims to determine the effectiveness and efficiency of various planting methods for paddy rice in East Wasile District, East Halmahera Regency, North Maluku Province. The analytical method uses multiple linear regression analysis, effectiveness of input allocation, production input allocation efficiency. The results showed that the effectiveness of the use of factors of production in paddy rice farming using the conventional method and jajar legowo is classified as not optimal because its effectiveness is below 80% and the efficiency of the use of factors of production in paddy rice farming using the conventional method and jajar legowo in East Wasile District, East Halmahera Regency, Maluku Province North is not yet efficient because the average value of the use of production facilities < 1.